2008
DOI: 10.2215/cjn.05311107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cysts in Seminal Tract and Abnormal Semen Parameters in Patients with Autosomal Dominant Polycystic Kidney Disease

Abstract: Conclusions: The presence of cysts in the seminal tract is remarkably high (43.47%); however, this finding does not correlate with sperm abnormalities, which are also a frequent finding, especially asthenozoospermia. This semen abnormality is probably related to the abnormal function of polycystins. More attention should be paid to reproductive aspects in the initial evaluation of patients with autosomal dominant polycystic kidney disease before their ability to conceive is further impaired by uremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Human ciliopathies like primary dyskinesia or autosomal dominant polycystic kidney disease can be associated with infertility [22,23]. There is only one report of male infertility due to NPHP in a family with homozygous NPHP4 truncating mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Human ciliopathies like primary dyskinesia or autosomal dominant polycystic kidney disease can be associated with infertility [22,23]. There is only one report of male infertility due to NPHP in a family with homozygous NPHP4 truncating mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This incidence of bilaterally is described as up to 43% in the literature (9). The ectopic ureter insertion into the seminal vesicle is extremely uncommon reported with accompanying by reflux and obstruction and therefore a primary adenocarcinoma could cause this (10).…”
Section: Discussionmentioning
confidence: 99%
“…Information on the clinical significance of these cysts is limited. Torra et al reported recently that the ratio of cysts in the seminal vesicles in ADPKD was 43% (4). They demonstrated that sperm abnormalities, although frequent, were not related to these cysts.…”
Section: Introductionmentioning
confidence: 96%